Rediscovering the Regency lute: a checklist of musical sources and extant instruments. (21st March 2018) - Takeuchi, Taro
Abstract: 'Awakening up, he took her hollow lute, — / Tumultuous, —and, in chords that tenderest be, / He played an ancient ditty, long since mute …'. These lines from The Eve of St Agnes, by John Keats, provide a reminder that the Romantic poets were fascinated by the lute. As if in response, around 1800 an instrument called 'lute' or 'modern lute' suddenly became fashionable. Most examples had an egg-shaped body, with ten single strings, and were built in London by craftsmen such as Buchinger, Barry and Harley. At the same time, older lutes from the 16th and 17th centuries were converted into 'modern lutes'. This article contributes to a rediscovery of these forgotten lutes and their music in the Regency period. It presents the first census of the nine extant instruments, surveys the original musical sources, and considers matters of playing technique and contemporary instruction books. A surprisingly rich repertory is revealed, for these lutes played arrangements of contemporary popular tunes and dances, but there were also newly composed sonatas, rondos and lute songs.